(untitled) (Patrimônio e Memória, 2015)
In the tale “Trevas no Paraíso", Trevas no paraíso – Histórias de amor e guerranosanos de chumbo, written byLuiz Fernando Emediato, the Araguaia Guerrilla repression context is built through the eyes of a narrator who goes withhis father, a political activist, to a trip to the heart of the guerrilla. The boy faces fragments of a social and historical reality that sees and does not understand well because he unawares the real purpose of the trip as well as the father’s identity. The look of the character and the other voices that appear in the tale, often in direct speech, opens the possibility of saying that the fiction several times simulate the structure of testimony, which was shrouded in official accounts of guerrillas. The tale becomes reconstitution, as much as testimony as memory, an individual story, the real catch, by citing historical context.